TVET a Kuala Krau Adventure UMPSA engages students with drone flight basic - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
KUALA KRAU, 11 October 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently launched an initiative to promote TVET among school students by organising the TVET@Kuala Krau Adventure.